Identification of Malassezia species using direct PCR-sequencing on clinical samples from patients with pityriasis versicolor and seborrheic dermatitis - Mahnaz Gholami; Fatemeh Mokhtari; Rasoul Mohammadi (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Malassezia yeasts are lipophilic normal flora of the skin in humans and other warm-blooded vertebrates. This genus includes 18 species and is responsible for dermatological disorders, such as pityriasis versicolor, atopic dermatitis, seborrheic dermatitis, folliculitis, and dandruff. The aim of the present study was to identify the etiologic agents of Malassezia infections among the patients referring to the Referral Dermatology Clinic of Al-Zahra Hospital, Isfahan, Iran, during 2018-2019. Materials and Methods: For the purpose of the study, clinical specimens, including skin scrapings and dandruff, were collected and subjected to direct microscopy, culture, and polymerase chain reaction (PCR) sequencing. Direct PCR was performed on the clinical samples to amplify the D1/D2 region of 26S rDNA, using specific primers; subsequently, the amplicons were sent for sequencing. Results: This study was conducted on 120 patients with suspected pityriasis versicolor and seborrheic dermatitis, who referred to the Referral Dermatology Clinic of Al-Zahra Hospital, Isfahan, Iran, during 2018-2019. Out of this population, 50 (41.7%), 26 (52%), and 24 (48%) cases had Malassezia infection, pityriasis versicolor, and seborrheic dermatitis, respectively. Malassezia globosa was found to be the most prevalent species (n=29, 58%), followed by M. restricta (n=20, 40%), and M. arunalokei (n=1, 2%). Conclusion: The epidemiologic study was indicative of the frequency of some Malassezia species, such as M. globosa and M. restricta, in Isfahan, Iran. It can be concluded that direct PCR on clinical samples could be used as a simple, precise, effective, fast, and affordable method for research and even routine medical mycology laboratory studies.